Application of functional imaging, neuronavigation, and intraoperative MR imaging in the surgical treatment of brain cavernomas - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2020)
Objective: The aim of this study was to investigate whether preoperative functional imaging and intraoperative magnetic resonance imaging (iMRI) facilitate surgery and improve outcomes in the surgical treatment of cavernous malformations of the brain (CM). Materials and Methods: Retrospective data analysis was performed for consecutive patients diagnosed with a CM who underwent surgical treatment at a single academic institution during a 12 year period. A total of 91 patients was eligible for analysis with a mean age of 38.8 ± 15 years (range 2–72 years). Altogether, 89.0% of CM had supratentorial and 11% infratentorial location. Results: Neuronavigation and iMRI was used in 69 (75.8%) patients with 28 (30.8%) of them together with functional MRI (fMRI) all in the supratentorial location. In 4.3% (3 cases) an intraoperative second-look surgery was performed. Altogether, a complete resection was achieved in 93% of the patients. In supratentorial surgeries, surgical times were significantly shorter in the fMRI group (p = 0.036), but altogether, infratentorial CM surgery took significantly longer (p = 0.014). Moreover, in the fMRI group, reduction of seizure medication was achieved significantly more often (p = 0.026). At an FU of 6.1± 3.1 years, 96% of the patients were assessed modified Rankin Scale 0 or 1. Conclusion: Neuronavigation together with intraoperative and functional MRI had a significant impact on resection amount, surgical time, and neurological and seizure outcome of supratentorial CM. In addition, iMRI was beneficial in few-selected cases.
CRIS-Team Scopus Importer:2020-11-27
Keywords: brain cavernomas; Functional imaging; intraoperative magnetic resonance imaging; neuronavigation

Risk Factors for Poor Postoperative Outcome and Epileptic Symptoms in Patients Diagnosed with Cerebral Cavernous Malformations - Winter, Fabian; Blair, Lisa; Buchfelder, Michael; Rössler, Karl (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Objective Roughly 12 to 47% of individuals with cerebral cavernous malformations (CCM) are asymptomatic, while other people may present with symptoms such as epileptic seizures, neurologic deficits, and intracerebral hemorrhages (IH). The aim of this study was to report our experience of postoperative outcomes of patients diagnosed with CCMs. Patients and Methods We present a series of consecutive patients who underwent surgical treatment for a diagnosed CCM between January 2003 and March 2014. Data were retrospectively analyzed with respect to preoperative visits, operating reports, patient admission charts, and postoperative follow-up visits. The Engel scale was used to evaluate the outcome of patients with epileptic seizures. Results A total of 91 patients were included with a mean age of 38.8 ± 15 years (range: 2-72 years). Prior to surgery, 57 of these patients had epileptic seizures, while 25 patients recorded at least one episode of IH with a latency time of 6.7 ± 8.5 years (range: 3-240 months) in between hemorrhages. A CCM located within the brainstem was significantly associated with IH prior to surgery (p = 0.000). If the CCM was adjacent to an eloquent brain area, the postoperative outcome in terms of seizure control was significantly worse (p = 0.033). In addition, a trend for worsened outcomes according to the Engel scale was observed in patients with more than one seizure prior to surgery (p = 0.055). Conclusion Proximity of CCMs to eloquent brain areas is a risk factor for poor postoperative outcome with respect to a lower rate of medication reduction as well as a lower rate of epileptic seizure omission. This underlines the importance of patient-specific therapeutic approaches.
CRIS-Team Scopus Importer:2020-12-25
Keywords: cavernoma; cerebral cavernous malformation; epileptic symptoms; outcome